Examining cognitive processes of unstructured decision making - Crow, Janis J. (Kansas State University, 2006)
Unstructured decision making is a dynamic process where an individual must create an alternative because one is not available or provided. In this type of a decision, an individual may not have formed preferences or may not know the path to arrive at a solution. As opposed to selecting from existing alternatives, little research examines when decision makers create an alternative. Electronic commerce websites allow individuals to create a product by customizing it. A web-based simulation called Interactive Choice was developed for the investigation. It is an interactive naturalistic decision space permitting experimental controls such as random placement of participants into conditions and random display of stimuli. Participants customized three products (pizza, cell phones, shoes). Building on theoretical foundations of unfolding model and Image Theory, a model asserts the presentation of the information and preparation of the decision maker influences a decision maker. A phased examination explores decision makers’ cognitive processes by measuring participants’ evaluations of the product created and the process to create it. In the first phase, three experiments find, contrary to previous independent investigations, participants rarely retain a pre-selected default value. Logistic regression reveals that the odds ratio of predicting default retention is dependent on product type. In the second phase, results identify that problem solving instructions influence decision making. Analyses of multidimensional scaling and cluster analysis reveal patterns for default retention and problem solving instructions that define an electronic decision aid called Choice Builder. The dissertation suggests that when an individual creates a product, he or she has more control over the process that subsequently reduces the influence of the default. A new theoretical foundation is proposed identifying that for unstructured decisions individuals construct both decision strategies and preferences while creating an alternative. With an active process of acquiring and evaluating information, an individual forms a decision strategy and updates preferences to achieve an ideal outcome. This dissertation makes four contributions that include 1) a research tool, Interactive Choice, for exploration, 2) the identification of cognitive processes involved, 3) a proposal of a new theoretical approach, and 4) an electronic decision aid, Choice Builder.
Keywords: Decision making; Internet; Customization; Consumer; Business Administration, Marketing (0338); Psychology, Cognitive (0633); Psychology, Experimental (0623)